Probing the Spin Dimensionality in Single‐Layer CrSBr Van Der Waals Heterostructures by Magneto‐Transport Measurements - Boix‐Constant, Carla; Mañas‐Valero, Samuel; Ruiz, Alberto M.; Rybakov, Andrey; Konieczny, Krzysztof Aleksander; Pillet, Sébastien; Baldoví, José J.; Coronado, Eugenio (Advanced materials (Weinheim), 2022)
2D magnetic materials offer unprecedented opportunities for fundamental and applied research in spintronics and magnonics. Beyond the pioneering studies on 2D CrI3 and Cr2Ge2Te6, the field has expanded to 2D antiferromagnets exhibiting different spin anisotropies and textures. Of particular interest is the layered metamagnet CrSBr, a relatively air‐stable semiconductor formed by antiferromagnetically‐coupled ferromagnetic layers (Tc∼150 K) that can be exfoliated down to the single‐layer. It presents a complex magnetic behavior with a dynamic magnetic crossover, exhibiting a low‐temperature hidden‐order below T*∼40 K. Here, the magneto‐transport properties of CrSBr vertical heterostructures in the 2D limit are inspected. The results demonstrate the marked low‐dimensional character of the ferromagnetic monolayer, with short‐range correlations above Tc and an Ising‐type in‐plane anisotropy, being the spins spontaneously aligned along the easy axis b below Tc. By applying moderate magnetic fields along a and c axes, a spin‐reorientation occurs, leading to a magnetoresistance enhancement below T*. In multilayers, a spin‐valve behavior is observed, with negative magnetoresistance strongly enhanced along the three directions below T*. These results show that CrSBr monolayer/bilayer provides an ideal platform for studying and controlling field‐induced phenomena in two‐dimensions, offering new insights regarding 2D magnets and their integration into vertical spintronic devices. The magneto‐transport properties of 2D CrSBr vertical van der Waals heterostructures are inspected, revealing a spontaneous spin alignment along the b‐axis together with spin‐reorientation and field‐induced phases. In multilayers, a spin‐valve behavior is observed with large negative magnetoresistance. This makes CrSBr of high interest not only as a new 2D magnetic model but also as a potential spintronic component.